Evaluation of a New Culture Protocol for Enhancing Fungal Detection Rates in Respiratory Samples of Cystic Fibrosis Patients - Tobias G.P. Engel; Marlou Tehupeiory-Kooreman; Willem J.G. Melchers; Monique H. Reijers; Peter Merkus; Paul E. Verweij (Journal of Fungi, 2020)
Cystic fibrosis (CF) can be complicated by fungal infection of the respiratory tract. Fungal detection rates in CF sputa are highly dependent on the culture protocol and incubation conditions and thus may lead to an underestimation of the true prevalence of fungal colonization. We conducted a prospective study to evaluate the additional value of mucolytic pre-treatment, increased inoculum (100 μL), additional fungal culture media (Sabouraud agar; SAB, Medium B+, Scedosporium selective agar; SceSel+ and Dichloran-Glycerol agar; DG18) and longer incubation time (3 weeks) compared with our current protocol. Using the new protocol, we prospectively analyzed 216 expectorated sputum samples from adult and pediatric CF patients (n = 77) and compared the culture yield to a three year retrospective cohort that used direct 10 μL loop inoculation on SAB with 5 days incubation (867 sputum samples/103 patients). Detection rates for molds increased from 42% to 76% (p < 0.0001). Twenty-six percent of cultures were polymicrobial in the prospective cohort as opposed to 4.7% in the retrospective cohort (p < 0.0001). Colonization rate with A. fumigatus increased from 36% to 57%. SAB and DG18 showed the highest detection rates for all molds (SAB 58.6%; DG18 56.9%) and DG18 had the best performance for molds other than A. fumigatus. The larger sample volume and longer incubation also contributed to the increased recovery of molds. The introduction of a modified fungal culture protocol leads to a major increase in detection rate and the diversity of molds, which influences fungal epidemiology and may have implications for treatment decisions.